Pharmacogenetic markers of colorectal cancer treatment. New approaches for cytostatic drugs efficacy estimation - N. B. Zakharzhevskaya; N. A. Kulemin; Ye. A. Babikova; Ye. B. Khomyakova; E. V. Generozov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze and present data of the foreign pharmacogenetic studies devoted to improvement of pharmacological therapy of colorectal cancer (CRC), in particular those, focused on the drugs with general cytostatic action: 5-fluorouracil derivatives, irinotecan and platinum agents.Summary. In the oncological diseases frequency spectrum CRC traditionally occupies the leading positions all over the world. The success of CRC chemotherapy depends significantly on the individual genetic features of the patient influencing both efficacy of pharmacological effects, and degree of side effects severity. If efficacy and necessity of pharmacogenetic investigation for such drugs of targeted therapy, as cetuximab, is already proven for the present time, it is still underestimated for the widely applied drugs of general cytostatic action. This review presents systematic and generalized data on the most informative genetic markers which analysis can be used for optimization of treatment of CRC patients at multicomponent modes of chemotherapy, such as FOLFIRI and FOLFOX.